Formulation-resolved VOC emission factors measured in a dynamic chamber and corresponding secondary formation potentials for selected architectural paints - Fanglin Wang; Ka Hei Lui; Donger Lai; Guoyang Lei; Chung Ling Man; Yansu He; Dasa Gu; Zhe Wang; Man Nin Chan; Donald R. Blake; Kin Fai Ho (Environmental Pollution, 2026)

Geospatial-based neighborhood hazards and asthma in adults: Interaction with social vulnerability - Yujing Chen; Farida S. Akhtari; David C. Fargo; Charles P. Scmitt; Vy Kim Nguyen; Kai Zhang; Evelyn Xiu Ling Loo; Peng Gao; Chao Jiang; Tzu-Hsuen Yuan; Martin Tsz-Ki Tsui; Lap Ah Tse; et al. (Journal of Hazardous Materials, 2026)

Associations between non-methane volatile organic compounds and cause-specific mortality across 14 major categories - Shengtao Wei; Ge Chen; Lan Chen; Zijun Yang; Fei Tian; Peng Hu; Kin Fai Ho; Shanshan Ran; Dashan Zheng; Hualiang Lin (Environmental Pollution, 2026)

Characterization of secondary organic aerosol (SOA) formation and toxicity from α-pinene photo-oxidation under effects of nitrogen oxides (NOx) and ammonia (NH3) - Ka Hei Lui; Tianhang Zhang; Fanglin Wang; Yik-Sze Lau; Steven Sai Hang Ho; Hsiao-Chi Chuang; Gehui Wang; Kin Fai Ho (Air Quality, Atmosphere & Health, 2026)

Exposome-wide associations and polyexposure risks of workplace chemical exposures on adult asthma: The Personalized Environment and Genes Study (PEGS) - Yujing Chen; Farida S. Akhtari; Yixuan He; Lihang Yu; Vy Kim Nguyen; Martin Tsz-Ki Tsui; Yuki Mizuno; William E. Funk; Crystal Ying Chan; Lap Ah Tse; Kin Fai Ho; Chirag J. Patel; et al. (Environmental Research, 2025)

The comparison between multiple linear regression and random forest model in predicting environmental noise and its frequency components level in Hong Kong using a land-use regression approach - Chui Hei Wong; Zhiyuan Li; Steve Hung Lam Yim; Ta-Yuan Chang; Chung Ling Man; Chin Ho Cheng; Timothy Chi-yui Kwok; Kin Fai Ho (Environmental Research, 2025)

Ambient air pollution exposure accelerates the occurrence of 78 non-communicable chronic diseases: an accelerated failure time analysis of a nationwide cohort - Fei Tian; Shengtao Wei; Zhengmin Qian; Jinde Zhao; Yuhua Wang; Kin-fai Ho; Lauren D. Arnold; Tom Burroughs; Hualiang Lin (GeroScience, 2025)

Characterization of chemical and bioreactivity properties of photooxidation reaction products from secondary organic aerosols (SOA) under high OH exposure condition - Ka Hei Lui; Xinye Zhu; Yik-Sze Lau; Tianhang Zhang; Gehui Wang; Hsiao-Chi Chuang; Kin Fai Ho (Atmospheric Environment, 2025)

Response to letter to editor re: Tran et al. 2024 (Huang et al.) - Huan Minh Tran; Feng-Jen Tsai; Kang-Yun Lee; Yuan-Hung Wang; Feng-Ming Yang; Shu-Chuan Ho; Hanh Thi My Bui; Linh Nhat Nguyen Hoang; Linh Thi My Bui; Kin-Fai Ho; Kian Fan Chung; Kai-Jen Chuang; et al. (Science of The Total Environment, 2025)

Corrigendum to ‘Extreme temperature increases the risk of COPD morbimortality: A systematic review and meta-analysis [Science of The Total Environment, Vol 958 [2025] 178087’ - Huan Minh Tran; Feng-Jen Tsai; Kang-Yun Lee; Yuan-Hung Wang; Feng-Ming Yang; Shu-Chuan Ho; Hanh Thi My Bui; Linh Nhat Nguyen Hoang; Linh Thi My Bui; Kin-Fai Ho; Kian Fan Chung; Kai-Jen Chuang; et al. (Science of The Total Environment, 2025)

Ambient temperature-related attributable risk for emergency asthma hospitalizations and length of stay in Hong Kong - Hong Qiu; Shengzhi Sun; Tze-Wai Wong; Xing Qiu; Kin-Fai Ho; Eliza Lai-Yi Wong (Urban Climate, 2025)

New mechanisms of PM2.5 induced atherosclerosis: Source dependent toxicity and pathogenesis - Xinyi Niu; Jinjin Yu; Jian Sun; Xinya Zhang; Lili Zhou; Xinyao Liu; Kun He; Zezhi Peng; Xiaofeng Niu; Hongmei Xu; Junji Cao; Kin-Fai Ho; et al. (Environmental Research, 2025)

Extreme temperature increases the risk of COPD morbimortality: A systematic review and meta-analysis - Huan Minh Tran; Feng-Jen Tsai; Kang-Yun Lee; Yuan-Hung Wang; Feng-Ming Yang; Shu-Chuan Ho; Hanh Thi My Bui; Linh Nhat Nguyen Hoang; Linh Thi My Bui; Kin-Fai Ho; Kian Fan Chung; Kai-Jen Chuang; et al. (Science of The Total Environment, 2025)

The association of air pollution with blood pressure, heart rate and stress among office workers using essential oils - Chien-Yu Lee; I-Jung Liu; Chih-Hong Pan; Lian-Yu Lin; Hsiao-Chi Chuang; Kin-Fai Ho; Chia-Huang Chang; Kai-Jen Chuang (Atmospheric Environment, 2024)

Integrating Doppler LiDAR and machine learning into land-use regression model for assessing contribution of vertical atmospheric processes to urban PM2.5 pollution - Yue Li; Tao Huang; Harry Fung Lee; Yeonsook Heo; Kin-Fai Ho; Steve H.L. Yim (Science of The Total Environment, 2024)

Characterization and toxicological effects of microplastics in PM2.5 in background sites of the southern coast of China - Jian Sun; Jiaer Yang; Steven Sai Hang Ho; Zezhi Peng; Xinyi Niu; Linli Qu; Ka Hei Lui; Hai Guo; Kin-Fai Ho (Atmospheric Environment, 2024)

A review on advancements in atmospheric microplastics research: The pivotal role of machine learning - Jiaer Yang; Zezhi Peng; Jian Sun; Zhiwen Chen; Xinyi Niu; Hongmei Xu; Kin-Fai Ho; Junji Cao; Zhenxing Shen (Science of The Total Environment, 2024)

A liquid culture method assisted by ATP analysis for accelerating laboratory experiments on ultraviolet disinfection of airborne bacteria - Kangqi Guo; Zhishang Wan; Yi Jiang; Kin-Fai Ho; Chun Chen (Journal of Hazardous Materials, 2024)

Corrigendum to ‘Personal exposure monitoring of fine and coarse particulate matter using exposure assessment models for elderly residents in Hong Kong’ [Chemosphere 357 (June 2024) 141975] - Ka Hei Lui; Tianhang Zhang; Chung Ling Man; Chi Shing Chan; Steven Sai Hang Ho; Linli Qu; Helen Hoi Ling Kwok; Timothy Chi Yui Kwok; Kin Fai Ho (Chemosphere, 2024)

The joint effect of long-term exposure to multiple air pollutants on non-accidental and cause-specific mortality: A longitudinal cohort study - Xianglin Wei; Kin Fai Ho; Tsung Yu; Changqing Lin; Ly-yun Chang; Dezhong Chen; Tony Tam; Bo Huang; Alexis K.H. Lau; Xiang Qian Lao (Journal of Hazardous Materials, 2024)

Personal exposure monitoring of fine and coarse particulate matter using exposure assessment models for elderly residents in Hong Kong - Ka Hei Lui; Tianhang Zhang; Chung Ling Man; Chi Shing Chan; Steven Sai Hang Ho; Linli Qu; Helen Hoi Ling Kwok; Timothy Chi Yui Kwok; Kin Fai Ho (Chemosphere, 2024)

Human pulmonary cytotoxicity of vehicular derived PM2.5: A study from three characterized tunnels - Xinyi Niu; Jinjin Yu; Ningning Zhang; Jian Sun; Kin-Fai Ho; Zhenxing Shen; Yu Huang; Junji Cao (Atmospheric Environment, 2024)

Formation of environmentally persistent free radicals and their risks for human health: a review - Xueying Wang; Haijiao Liu; Yonggang Xue; Long Cui; Long Chen; Kin-fai Ho; Yu Huang (Environmental Chemistry Letters, 2024)

Exposure to BTEX is associated with cardiovascular disease, dyslipidemia and leukocytosis in national US population - Yansu He; Hong Qiu; Wenqiao Wang; Yong Lin; Kin Fai Ho (Science of The Total Environment, 2024)

Effects of long-term indoor air purification intervention on cardiovascular health in elderly: a parallel, double-blinded randomized controlled trial in Hong Kong - Xi Xia; Ka Hung Chan; Timothy Kwok; ShaoWei Wu; Chung Ling Man; Kin-Fai Ho (Environmental Research, 2024)

Characteristics and sources of oxygenated VOCs in Hong Kong: Implications for ozone formation - Fanglin Wang; Steven Sai Hang Ho; Chung Ling Man; Linli Qu; Zhe Wang; Zhi Ning; Kin Fai Ho (Science of The Total Environment, 2024)

Characterization of a smog chamber for studying formation of gas-phase products and secondary organic aerosol - Qi Yuan; Zhuozhi Zhang; Meng Wang; Kin Fai Ho; Tao Wang; Shuncheng Lee (Journal of Environmental Sciences, 2024)

Origin and transformation of volatile organic compounds at a regional background site in Hong Kong: Varied photochemical processes from different source regions - Qi Yuan; Zhuozhi Zhang; Yi Chen; Lirong Hui; Meng Wang; Men Xia; Zhouxing Zou; Wan Wei; Kin Fai Ho; Zhe Wang; Senchao Lai; Yingyi Zhang; et al. (Science of The Total Environment, 2024)

High spatial resolution estimates of major PM2.5 components and their associated health risks in Hong Kong using a coupled land use regression and health risk assessment approach - Zhiyuan Li; Steve Hung Lam Yim; Xiao He; Xi Xia; Kin-Fai Ho; Jian Zhen Yu (Science of The Total Environment, 2024)

Characterising personal, household, and community PM2.5 exposure in one urban and two rural communities in China - Ka Hung Chan; Xi Xia; Cong Liu; Haidong Kan; Aiden Doherty; Steve Hung Lam Yim; Neil Wright; Christiana Kartsonaki; Xiaoming Yang; Rebecca Stevens; Xiaoyu Chang; Dianjianyi Sun; et al. (Science of The Total Environment, 2023)

The joint association of ambient air pollution and different sleep posture with mild obstructive sleep apnea: A study conducted at Taipei Sleep Center - Yansu He; Wen-Te Liu; Shangyang Lin; Zhiyuan Li; Hong Qiu; Steve Hung Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Evaluation of intervention measures in reducing the driver's exposure to respiratory particles in a taxi with infected passengers - Yue Pan; Wenjie Huang; Ho Kam Dai; Ye Bian; Kin-Fai Ho; Chun Chen (Science of The Total Environment, 2023)

Investigation of the multi-year trend of surface ozone and ozone-precursor relationship in Hong Kong - Xin Feng; Jia Guo; Zhe Wang; Dasa Gu; Kin-Fai Ho; Yi Chen; Kezheng Liao; Vincent T.F. Cheung; Peter K.K. Louie; Kenneth K.M. Leung; Jian Zhen Yu; Jimmy C.H. Fung; et al. (Atmospheric Environment, 2023)

Far-UVC disinfection of airborne and surface virus in indoor environments: Laboratory experiments and numerical simulations - Kangqi Guo; Yue Pan; Hoi Fung Ronaldo Chan; Kin-Fai Ho; Chun Chen (Building and Environment, 2023)

Developing a survival probability-based Lagrangian model for predicting ultraviolet disinfection of bioaerosols in enclosed environments - Yue Pan; Kangqi Guo; Chao-Hsin Lin; Daniel Wei; Kin-Fai Ho; Chun Chen (Building and Environment, 2023)

Air pollution exacerbates mild obstructive sleep apnea by disrupting nocturnal changes in lower-limb body composition: a cross-sectional study conducted in urban northern Taiwan - Yansu He; Wen-Te Liu; Shang-Yang Lin; Zhiyuan Li; Hong Qiu; Steve Hung-Lam Yim; Hsiao-Chi Chuang; Kin Fai Ho (Science of The Total Environment, 2023)

Hippo signaling pathway contributes to air pollution exposure-induced emphysema in ageing rats - Vincent Laiman; Ta-Chih Hsiao; Yu-Ting Fang; You-Yin Chen; Yu-Chun Lo; Kang-Yun Lee; Tzu-Tao Chen; Kuan-Yuan Chen; Shu-Chuan Ho; Sheng-Ming Wu; Jen-Kun Chen; Didik Setyo Heriyanto; et al. (Journal of Hazardous Materials, 2023)

Low-dose blood BTEX are associated with pulmonary function through changes in inflammatory markers among US adults: NHANES 2007–2012 - Yansu He; Yong Lin; Hong Qiu; Linying Wu; Kin Fai Ho (Environmental Science and Pollution Research, 2023)

Effects of indoor air purification intervention on blood pressure, blood‑oxygen saturation, and heart rate variability: A double-blinded cross-over randomized controlled trial of healthy young adults - Xi Xia; Xinyi Niu; Kahung Chan; Hongmei Xu; ZhenXing Shen; Jun-ji Cao; ShaoWei Wu; Hong Qiu; Kin-Fai Ho (Science of The Total Environment, 2023)

Health benefits from substituting raw biomass fuels for charcoal and briquette fuels: In vitro toxicity analysis - Xinyi Niu; Xinyao Liu; Bin Zhang; Qian Zhang; Hongmei Xu; Hongai Zhang; Jian Sun; Kin-Fai Ho; Hsiao-Chi Chuang; Zhenxing Shen; Junji Cao (Science of The Total Environment, 2023)

Ambient relative humidity-dependent obstructive sleep apnea severity in cold season: A case-control study - Kuan-Jen Bai; Wen-Te Liu; Yuan-Chien Lin; Yansu He; Yueh-Lun Lee; Dean Wu; Ta-Yuan Chang; Li-Te Chang; Chun-Yeh Lai; Cheng-Yu Tsai; Kian Fan Chung; Kin-Fai Ho; et al. (Science of The Total Environment, 2023)

Oxygen vacancy mediated α-MoO3 bactericidal nanocatalyst in the dark: Surface structure dependent superoxide generation and antibacterial mechanisms - Qin Gao; Zhenyu Wang; Yongfang Rao; Yulei Zhao; Junji Cao; Kin-Fai Ho; Yue Zhai; Mingyu Xiong; Juntang Li; Yu Huang (Journal of Hazardous Materials, 2023)

Associations of personal exposure to domestic heating and cooking fuel emissions and epidemiological effects on rural residents in the Fenwei Plain, China - Yunxuan Gu; Hongmei Xu; Rong Feng; Yue Cheng; Bei Han; Kin Fai Ho; Zexuan Wang; Yansu He; Linli Qu; Steven Sai Hang Ho; Jian Sun; Zhenxing Shen; et al. (Science of The Total Environment, 2023)

Toxicological effects of fresh and aged gasoline exhaust particles in Hong Kong - Yik-Sze Lau; Hon-Yin Poon; Bruce Organ; Hsiao-Chi Chuang; Man-Nin Chan; Hai Guo; Steven Sai Hang Ho; Kin-Fai Ho (Journal of Hazardous Materials, 2023)

Individual socioeconomic status as a modifier of the association between high ambient temperature and hospital admissions: a time series study in Hong Kong, 2010–2019 - Yi Tong Guo; William Bernard Goggins; Emily Ying Yang Chan; Kin Fai Ho (Environmental Science and Pollution Research, 2022)
Few studies have examined individual socioeconomic status (SES) as a potential modifier of ambient temperature–health associations, especially for temperature-related hospitalizations. We fit penalized distributed lag non-linear models within generalized additive models to study the short-term associations (0–3 days) between temperature and hospital admissions stratified by common causes, age, and individual SES, as determined by whether patients received public assistance (PA) to cover their medical fee at the time of hospitalizations, during the hot season (May 15 to October 15) in Hong Kong for the years 2010–2019. We calculated the ratio of relative risk (RRR) and corresponding 95% confidence interval (CI) to statistically test the difference of the associations between PA groups. For 75 + patients, the PA group had significantly increased risks of hospitalizations at higher temperature for most causes, with relative risks (RR, 99th %ile vs. 25%ile) and 95% CIs of 1.138 (1.099, 1.179), 1.057 (1.008, 1.109), and 1.163 (1.094, 1.236) estimated for all non-cancer non-external, circulatory, and respiratory admissions, respectively. There were slight decreases of RRs with higher temperature for 75 + patients without PA. The strengths of temperature–hospitalization associations were strongly and significantly different between PA groups for all examined causes for 75 + patients, with the most considerable discrepancy found for ischemic heart disease (RRR = 1.266; 95% CI, 1.137, 1.410). Hospitalizations for patients aged 15–74 were less affected by heat, and the difference of the associations between groups was small. Individual SES is a significant modifier of high temperature–hospitalization associations in Hong Kong among the elderly. Public health interventions are needed to better protect this subpopulation from adverse health impacts of high temperature.

Air pollution associated with cognitive decline by the mediating effects of sleep cycle disruption and changes in brain structure in adults - Chen-Chen Lo; Wen-Te Liu; Yueh-Hsun Lu; Dean Wu; Chih-Da Wu; Ting-Chieh Chen; Yu-Ting Fang; Yu-Chun Lo; You-Yin Chen; Lo Kang; Cheng-Yu Tsai; Yueh-Lun Lee; et al. (Environmental Science and Pollution Research, 2022)

Health risks of adults in Hong Kong related to inhalation of particle-bound heavy metal(loid)s - Xiaocui Chen; Tony J. Ward; Chinmoy Sarkar; Kin-Fai Ho; Chris Webster (Air Quality, Atmosphere & Health, 2022)
Heterogeneity between ambient and personal exposure to heavy metals has been documented. However, few studies have investigated potential health risks posed by inhalational exposure to airborne heavy metal(loid)s at the individual level. A total of 404 personal fine particles (PM 2.5 ) samples were collected from 61 adult residents (aged 18–63 years) in Hong Kong during 2014–2015. Heavy metal(loid)s were analyzed using energy dispersive X-ray fluorescence. Among the analyzed heavy metal(loid)s, zinc (Zn) was the most abundant component in personal PM 2.5 , followed by lead (Pb), copper (Cu), and vanadium (V); cobalt (Co) and cadmium (Cd) were not detectable. Health risks of personal exposure to heavy metal(loid)s via inhalation were assessed for adults, including non-cancer risks that were characterized by hazard quotient (HQ) and hazard index (HI). The results indicated that non-cancer risks of heavy metal(loid)s were attributable to Cu, with a 95 th HQ value > 1. Arsenic (As) and hexavalent chromium [Cr (VI)] were also significant contributors to inhalation cancer risks (> 1 × 10 −6 ) for the adult participants. Finally, we employed a Monte Carlo simulation to evaluate the uncertainty associated with health risk assessment. The mean and median upper-bound lifetime cancer risk associated with inhalation exposure to carcinogenic heavy metal(loid)s exceeded the acceptable level (1 × 10 −6 ) for adults. Traffic emission (including non-tailpipe exhaust), shipping emission, and regional pollution were significant sources of heavy metals. These findings suggest that emission controls targeting local vehicles and vessels should be given priority in Hong Kong.

Organic carbon and acidic ions in PM2.5 contributed to particle bioreactivity in Chinese megacities during haze episodes - Kin-Fai Ho; Ya-Chun Lee; Xinyi Niu; Hongmei Xu; Renjian Zhang; Jun-Ji Cao; Cheng-Yu Tsai; Ta-Chih Hsiao; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2022)

Loss of E-cadherin due to road dust PM2.5 activates the EGFR in human pharyngeal epithelial cells - Nguyen Thanh Tung; Kin-Fai Ho; Xinyi Niu; Jian Sun; Zhenxing Shen; Feng Wu; Junji Cao; Hoang Ba Dung; Tran Phan Chung Thuy; Ta-Chih Hsiao; Wen-Te Liu; Hsiao-Chi Chuang (Environmental Science and Pollution Research, 2021)

Characterization of chemical components and cytotoxicity effects of indoor and outdoor fine particulate matter (PM2.5) in Xi’an, China - Xinyi Niu; Kin Fai Ho; Tafeng Hu; Jian Sun; Jing Duan; Yu Huang; Ka Hei Lui; Junji Cao (Environmental Science and Pollution Research, 2019)

Investigation of factors affecting the gaseous and particulate matter emissions from diesel vehicles - Bei Wang; Yik-Sze Lau; Yuhan Huang; Bruce Organ; Shun-Cheng Lee; Kin-Fai Ho (Air Quality, Atmosphere & Health, 2019)

Seasonal behavior of water-soluble organic nitrogen in fine particulate matter (PM2.5) at urban coastal environments in Hong Kong - Steven Sai Hang Ho; Lijuan Li; Linli Qu; Junji Cao; Ka Hei Lui; Xinyi Niu; Shun-Cheng Lee; Kin Fai Ho (Air Quality, Atmosphere & Health, 2019)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

Who is more vulnerable to death from extremely cold temperatures? A case-only approach in Hong Kong with a temperate climate - Hong Qiu; Linwei Tian; Kin-fai Ho; Ignatius T. S. Yu; Thuan-Quoc Thach; Chit-Ming Wong (International Journal of Biometeorology, 2016)

Concentrations, particle-size distributions, and indoor/outdoor differences of polycyclic aromatic hydrocarbons (PAHs) in a middle school classroom in Xi’an, China - Hongmei Xu; Benjamin Guinot; Xinyi Niu; Junji Cao; Kin Fai Ho; Zhuohui Zhao; Steven Sai Hang Ho; Suixin Liu (Environmental Geochemistry and Health, 2015)

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong - Linwei Tian; Sarah R. Hossain; Hualiang Lin; Kin Fai Ho; Shun Cheng Lee; Ignatius T. S. Yu (Environmental Geochemistry and Health, 2011)

Positive sampling artifacts in particulate organic carbon measurements in roadside environment - Yan Cheng; Shun Cheng Lee; Kin Fai Ho; Kochy Fung (Environmental Monitoring and Assessment, 2010)

Cloning and characterization of chironomidae ferrochelatase: Copper activation of the purified ferrochelatase - Yuet Kin Leung; Kwong Fai Wong; Hung Kay Lee; John W. Ho (Molecular and Cellular Biochemistry, 2004)